The Role of the Competition Policy in Forging the European Common Market - Radu-Cristian Musetescu; Alina Dima; Cristian Păun (Romanian Journal of European Affairs, 2008)
The forging of the Single Market represents the most important dimension of the first pillar of the European Union, which is the European Community. It can be argued that, as compared to the other two pillars (the Common Foreign and Security Policy and the Police and Judicial Cooperation in the Criminal Matters), it has the most powerful impact on the welfare of European citizens. The European policy makers define however the Internal Market as not only an economic area where there are no more state-imposed barriers in the path of the freedom of movement of goods and services at the borders of the member-states but also a single business environment where there are a single currency, coordinated economic policies as well as homogeneous business practices of private undertakings. In this process, despite a large set of common policies, the competition policy has reached the status of the building block of the Common Market.